Antibacterial Effectivity of Nanoemulgel Phaleria macrocarpa’s leaf on the Porphyromonas gingivalis ATCC 33277 Biofilm Thickness - Pratiwi, Rosa; Ratnawati, Irma Dewi; Ismail, Ade; Nurhapsari, Arlina; Amelia, Rosalita (Odonto : Dental Journal, 2024)
Porphyromonas gingivalis is an oppoturnistic microorganism in periodontal disease that is formed at the stage maturation of biofilm formation. One of the natural materials biofilm reduction is the Phaleria macrocarpa. Phaleria macrocarpa’s leaf contains chemical compounds such as flavonoids, tannins, alkaloids, saponins that function as antibacterials.The aim of this research is to determine the effectiveness of the nanoemulsion of the gel Phaleria macrocarpa’s leaf  on the thickness of the P. gingivalis bacterial biofilm. The research design was carried out with a post test only with a total of 28 samples, then divided into 4 groups of treatment of Phaleria macrocarpa’s leaf extract nanoemulsion gel preparations with variations in concentrations of 30%, 40%, and 50%, as well as a control group of 25% metronidazole gel. The reading of the anti-biofilm thickness test results was measured by OD (Optical density) using an ELISA-reader. One way Anova parametric test among obtained p<0.000 results showing the effect of Phaleria macrocarpa’ leaf gel nanoemulsion extract on the decrease in the thickness of the Porphyromonas gingivalis bacterial biofilm. It can be concluded that the nanoemulsion gel formulation of Phaleria macrocarpa’s leaf extract concentrations of 30%, 40%, and 50% is effective, with a concentration 50% was most effective against reducing the thickness of the bacterial biofilm Porphyromonas gingivalis.